2017
DOI: 10.1111/jdv.14730
|View full text |Cite
|
Sign up to set email alerts
|

Associations between air pollution, climate factors and outpatient visits for eczema in West China Hospital, Chengdu, south‐western China: a time series analysis

Abstract: This study provides evidence that environmental factors like relative humidity and multiple air pollutants influence the incidence and prevalence of eczema and have lagged effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 50 publications
8
55
5
Order By: Relevance
“…Air pollutants were found to have harmful effects on AD in our study, which was consistent with previous studies . We compared our results with a very similar study done in Chengdu, south‐western China . As shown in Table , both our study and the study in Chengdu investigate the associations between air pollution and outpatients for AD (eczema) during 5 years.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Air pollutants were found to have harmful effects on AD in our study, which was consistent with previous studies . We compared our results with a very similar study done in Chengdu, south‐western China . As shown in Table , both our study and the study in Chengdu investigate the associations between air pollution and outpatients for AD (eczema) during 5 years.…”
Section: Discussionsupporting
confidence: 90%
“…However, different lag effect periods were found in previous studies and for different pollutants. The similar study in Chengdu, China found the greatest effects of air pollution at lag1 . The above panel study in Korea found the effects of PM10 were the greatest at lag0–5 (moving averages of 5 days) while the effects of NO 2 were the greatest at lag0 .…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This was found in a study from China, where the numbers of outpatient visits for eczema were compared to environmental conditions including air pollution, wind and humidity. It was found that both dryness, but also increased air pollution, led to an increase in eczema visits in ChengDu West China …”
Section: Environmental Influence On the Skinmentioning
confidence: 99%